Burden of non-adherence to latent tuberculosis infection drug therapy and the potential cost-effectiveness of adherence interventions in Canada: a simulation study. Issue 9 (15th September 2017) - Patel, Anik R; Campbell, Jonathon R; Sadatsafavi, Mohsen; Marra, Fawziah; Johnston, James C; Smillie, Kirsten; Lester, Richard T
Abstract : Objective: Pharmaceutical treatment of latent tuberculosis infection (LTBI) reduces the risk of progression to active tuberculosis (TB); however, poor adherence tempers the protective effect. We aimed to estimate the health burden of non-adherence, the maximum allowable cost of hypothetical new adherence interventions to be cost-effective and the potential value of existing adherence interventions for patients with low-risk LTBI in Canada. Design: A microsimulation model of LTBI progression over 25 years. Setting: General practice in Canada. Participants: Individuals with LTBI who are initiating drug therapy. Interventions: A hypothetical intervention with a range of effectiveness was evaluated. Existing drug adherence interventions including peer support, two-way text messaging support, enhanced adherence counselling and adherence incentives were also evaluated. Primary and secondary outcome measures: Simulation outcomes included healthcare costs, TB incidence, TB deaths and quality-adjusted life years (QALYs). Base case results were interpreted against a willingness-to-pay threshold of $C50 000/QALY. Results: Compared with current adherence levels, full adherence to LTBI drug therapy could reduce new TB cases from 90.3 cases per 100 000 person-years to 35.9 cases per 100 000 person-years and reduce TB-related deaths from 7.9 deaths per 100 000 person-years to 3.1 deaths per 100 000 person-years. An intervention that increases relative adherence by 40% would bring the population near full adherence to drug therapy and could have a maximum allowable annual cost of approximately $C450 per person to be cost-effective. Based on estimates of effect sizes and costs of existing adherence interventions, we found that they yielded between 900 and 2400 additional QALYs per million people, reduced TB deaths by 5%–25% and were likely to be cost-effective over 25 years. Conclusion: Full adherence could reduce the number of future TB cases by nearly 60%, offsetting TB-related costs and health burden. Several existing interventions are could be cost-effective to help achieve this goal.